China Satellite Navigation Conference (CSNC 2021) proceedings volume III - Yang, Changfeng; Xie, Jun (Singapore Springer, 2021)
China Satellite Navigation Conference (CSNC 2021) Proceedings presents selected research papers from CSNC 2021 held during 22nd-25th, 2021 May in Nanchang, China. These papers discuss the technologies and applications of the Global Navigation Satellite System (GNSS), and the latest progress made in the China BeiDou System (BDS) especially. They are divided into 10 topics to match the corresponding sessions in CSNC2021 which broadly covered key topics in GNSS. Readers can learn about the BDS and keep abreast of the latest advances in GNSS techniques and applications.
Professional GNSS Applications -- GNSS Applications for the Mass Market -- GNSS and Their Augmentations -- Satellite Orbits and Precise Positioning -- Time Frequencies and Precision Timing -- Autonomous Navigation and Intelligent Operation -- GNSS Signal Processing -- GNSS User Terminals -- PNT Architectures and New PNT Technologies -- Policies Standards and Intellectual Property Rights.
Electronic reproduction
Keywords: Artificial satellites in navigation -- Congresses; Electronic books